Factors that Influence the Effectiveness of Bureaucratic Reform Mediated by Digital Literacy - Desmon Sharon; Benni Sutanto (CV Putra Publisher, 2026)
This study aims to analyze the factors influencing the effectiveness of bureaucratic reform with digital literacy as a mediating variable at the Communication, Informatics, Encryption, and Statistics Office of Indragiri Hilir Regency. The variables examined in this study include employe innovation and Dynamic Capabilities as independent variables, digital literacy as a mediating variable, and the effectiveness of bureaucratic reform as a dependent variable. The theoretical foundation of this research is built on the Dynamic Capabilities Theory developed by Teece, Pisano, and Shuen, as well as the organizational innovation theory formulated by Rogers thru the Diffusion of Innovations. This research uses a quantitative approach with a survey method. The research population includes all employes of the institution, with the sampling technique using the census method so that the entire population is made the research respondents. Data were collected thru questionnaires using a Likert scale and analyzed using the Partial Least Square-based Structural Equation Modeling (SEM-PLS) method with the help of SmartPls software. The research results show that employe innovation has a positive and significant impact on digital literacy as well as on the effectiveness of bureaucratic reform. Dynamic Capabilities have also been proven to have a positive and significant impact on digital literacy and the effectiveness of bureaucratic reform. Additionally, digital literacy has been shown to significantly affect the effectiveness of bureaucratic reform and to mediate the relationship between employe innovation and Dynamic Capabilities on the effectiveness of bureaucratic reform. These findings indicate that the enhancement of employe innovation capacity and organizational Dynamic Capabilities, supported by the strengthening of digital literacy, are determinant factors in achieving effective bureaucratic reform, particularly in the context of the digital transformation of local government